Giant pancreatic solid cystic desmoid tumor with two ectopic adrenal tissues - Neşe Ekinci; Fikret Dirilenoğlu; Arzu Avcı; Oğuzhan Özsay (Turkish Journal of Gastroenterology, 2019)
A 19-year-old woman presented with painless swelling of the abdomen. During surgery, a giant mass measuring 37 cm×26 cm×12 cm within the distal pancreas invading the spleen was noted. The clinical diagnosis of a solid cystic pseudopapillary tumor of the pancreas was suspected. Distal pancreatectomy, splenectomy, and debulking surgery were performed. Histological examination showed that the tumor infiltrated the spleen and pancreatic parenchyma, and sections of the solid areas revealed a proliferation of spindle-shaped or stellate cells growing in fascicular and storiform patterns within a myxoid intercellular matrix. Cystic areas were representing the entrapped excretory pancreatic ductules. Interestingly, there were two ectopic adrenal tissues found incidentally in the peripheral portion of the tumor. The histopathologic and immunohistochemical features were consistent with a solid cystic desmoid tumor of the pancreas. Desmoid tumors of the pancreas are very rare, and if they present as a solid cystic lesion, their diagnosis may be difficult. We report the case for its rarity and huge size and to emphasize a regular follow-up because the long-term prognosis is currently unknown. Cite this article as: Ekinci N, Dirilenoğlu F, Avcı A, Ozsay O. Giant pancreatic solid cystic desmoid tumor with two ectopic adrenal tissues. Turk J Gastroenterol 2017; 28: 401-4.